TINGKAT KERUSAKAN TEGAKAN HUTAN AKIBAT OPERASI PENEBANGAN PADA DUA HAK PENGUSAHAAN HUTAN DI KALIMANTAN BARAT - Jurnalis Thaib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Minimum level of stand damages is one of the obyectives of the tropical rain forest harvesting practices in which the Indonesian Selective Cutting system is applied. In order to meet that obyective, various manuals should be prepared based on sound quantitative data.Observation on stand damages due to felling operations has been carried out in Suka Jaya Makmur Enterprise (SJM) and Kawedar Mukti Timber Enterprise (KMT), both located in West Kalimantan. The stand damages caused by felling one tree vary from 3 to 8 trees with an average of 6 trees in SJM, and from 2 to 7 trees with an average of 4 trees in KMT. The relationships between stand damage (Y) and stand density (X) are: Y = -4,69 + 0,08 X for SJM and Y = -6,83+ 0,08 X for KMT.The results of the study showed that the major causes of the variation of stand damages are improper direction of tree felling, and less control from supervisors/managers.